2017
DOI: 10.1002/jms.3880
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the structure of sequence‐defined poly(phosphodiester)s for optimal MS/MS reading of digital information

Abstract: Sequence‐controlled polymers are synthetic macromolecules composed of co‐monomers arranged in a precise manner. When defined as letters of an alphabet such as the 0/1 bits of the ASCII code, building units can be used to store information at the molecular level. So‐encoded messages can be read by MS/MS sequencing which complexity, however, highly depends on the polymer backbone chemistry. In this perspective special feature article, Laurence Charles, Jean‐François Lutz and co‐authors show that the structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Besides the investigation of enhanced synthetic approaches, which further increase the degree of control, the potential applications of such defined structures gain increasing attention 16 . Particularly, the application in the field of data storage has been discussed in detail 2,31,32,[36][37][38][39][40] . The data storage capacity of DNA serves as prototype as it carries the genetic code 18,19 .…”
mentioning
confidence: 99%
“…Besides the investigation of enhanced synthetic approaches, which further increase the degree of control, the potential applications of such defined structures gain increasing attention 16 . Particularly, the application in the field of data storage has been discussed in detail 2,31,32,[36][37][38][39][40] . The data storage capacity of DNA serves as prototype as it carries the genetic code 18,19 .…”
mentioning
confidence: 99%
“…In contrast, an additional MS‐active group was introduced into the end‐group of sequence‐controlled polyurethanes to improve their ionization yield, another key requirement for reliable sequencing by MS/MS 14 . In order to capitalize on the robustness of the phosphoramidite used in the automated synthesis of long poly(phosphodiester)s, specific reagents were prepared to include alkoxyamine linkages in the final chains, the low bond dissociation energy of which makes all phosphate bonds MS/MS‐silent, lowering the number of product ion series from eight to two and hence ensuring full sequence coverage of long chains 15 . Similarly, Zhang and co‐workers recently showed that controlling the oxidation degree of sulfur atoms in the backbone of poly(succinimide thioester)s drastically enhances dissociation selectivity 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Beside the nature of coding moiety, two main strategies can be envisaged to design the polymeric skeleton. One can first focus on developing synthesis protocols for production of highly monodisperse samples of long polymeric chains, which molecular structure can be further optimized to ensure their MS/MS readability [11]. For example, this approach was successfully implemented for sequence-defined poly(phosphodiester)s. These species were first synthesized as defect-free chains with degrees of polymerization (DP) above 100 using an automated synthesis protocol to implement phosphoramidite chemistry [12].…”
Section: Introductionmentioning
confidence: 99%